UNDERSTANDING FLOW PATHWAYS, MAJOR CHEMICAL TRANSFORMATIONS AND WATER SOURCES USING HYDROCHEMICAL DATA IN A CONSTRUCTED FEN, ALBERTA CANADA. - Biagi, Kelly (My University, 2015)
Bitumen extraction in the Athabasca oil sands causes significant disturbance of landscapes originally rich in wetland and forest ecosystems, which now require reclamation as mandated by the Alberta Government. However, most research to date has focused on upland-forest ecosystems with little attention on wetland-peatland ecosystems, which are considered more challenging to construct due to salinization potential from ubiquitous salts used in the oil sands extraction and treatment processes; with particular focus on elevated Na+ due to its detrimental ecological effects. Syncrude Canada Ltd. (SCL) has constructed an upland-wetland system, the Sandhill Fen Watershed (SFW), to advance the understanding of wetland reclamation in the oil-sands region. The SFW is a highly engineered and managed system. Water is supplied from an artificial fresh water source and drainage is enhanced through a constructed surface outlet and an under-drain system intended to provide a downward hydraulic gradient to inhibit the upward movement of salts from the underlying waste material. The objective of this research is to understand the hydrochemical response of the SFW to variations in hydrological management with respect to sources, flow pathways and major chemical transformations of water as it moves throughout SFW. Through surface and pore water sampling, the electrical conductivity and major ions were measured throughout the growing season of 2013 and 2014. Results indicate that the combination of freshwater inflow, flushing of the system with the outflow pump and open underdrains in 2013 kept the overall salinity within the SFW relatively low, with most lowland sites under 1000 µS/cm. Major ion results indicate that most water throughout the SFW classified as Ca-HCO3 or Ca-SO4 in 2013, with higher concentrations in the uplands however Na+ concentrations did not exceed 250 mg/L at any sampling sites. With minimal management in 2014 and consequent limited freshwater input and flushing of the system, the overall salinity of the SFW increased considerably and EC at most sites in lowlands exceeded 1000 µS/cm. Na+, Ca+2, SO4-2 and HCO3- concentrations increased across the SFW, with higher concentrations in the uplands than the lowlands. Although most sites classified as Ca-SO4, the most notable change in 2014 was the presence of several Na+ “hotspots” along the southern hummocks in the SFW, where water samples classified as Na-SO4 and Na+ concentrations reached as high as 886 mg/L. Results provides evidence of modelled upward movement of Na+ from underlying waste materials and subsequent seepage from hummocks with limited pump management in the SFW.
Keywords: Hydrology, reclamation, oil sands, salinity, sodium, fen, constructed fen